Leveraging computer-mediated marketing environments - Bowen, Gordon, 1950-; Ozuem, Wilson, 1974- (Business Science Reference, 2019)
"This book discusses the nature of heightened interaction between marketers and consumers in the evolving technological environments, particularly on the central nature of online communities and other emerging technologies on dialogic engagement. It also examines the relevant roles of online communities and emerging technologies in creating and retaining customers through effective dialogue management"--